Social factors associated to binge drinking: a cross-sectional survey among Brazilian students in private high schools - Locatelli Danilo P; Moura Yone G; Opaleye Emerita S; Martins Silvia S; Sanchez Zila M; Noto Ana R (BMC, 2011)
Abstract Background Binge drinking (BD) seems to be related to health and social complications among adolescents. Considering that knowledge about BD in developing countries is limited and that in Brazil high socioeconomic status is a risk factor for alcohol abuse, this study sheds light about this phenomenon among adolescents from a different cultural background than prior North-American and European studies. Methods Brazilian students (n = 2691) selected through a representative, stratified and clustered sampling method were asked to answer a self-report questionnaire. The questionnaire contained questions about patterns of alcohol consumption, religious beliefs, leisure activities, family structure and relationships. Data were analyzed with basic contingency tables with Chi-square tests followed by a decision tree analysis and weighted logistic regression. Results Almost thirty-five percent of the students reported recent binge drinking. BD in the past month was positively associated with older age (aOR = 1.5[1.2-1.7]), male gender (aOR = 1.5[1.2-2.0]) going out with friends almost every night (aOR = 33.9[14.2-80.7]), not living with mother (aOR = 2.4[1.3-4.7]), believing in God with little conviction (aOR = 1.6[1.2-2.0]) and rarely talking to parents about anything (aOR = 1.7[1.3-2.2]) or always about drugs (aOR = 1.8[1.3-2.5]). Factors inversely associated with BD were: paying lower monthly tuition fees (aOR = 0.5[0.4-0.9]), living with people who do not get drunk (aOR = 0.6[0.4-0.7]) and frequent engagement in worships (aOR = 0.7[0.5-0.9]). Conclusion The habit of BD in adolescents enrolled in private high schools in Brazil is strongly linked to the frequency with which they go out with friends at night. Factors such as religiosity, expressed by trust in God and participation in worship, and being enrolled in a school with cheaper tuition fees were associated with avoidance of BD in this population.